Inflammation and endothelial function relevant genetic polymorphisms, carotid atherosclerosis, and vascular events in high-risk stroke population - Chen, Hong; Qing, Ting; Luo, Hua; Yu, Ming; Wang, Yanfen; Wei, Wei; Xie, Yong; Yi, Xingyang (Frontiers in Neurology, 2024)
Aim To identify the associations of 19 single nucleotide polymorphisms (SNPs) in genes involved in inflammation and endothelial function and carotid atherosclerosis with subsequent ischemic stroke and other vascular events in the high-risk stroke population. Methods This was a multicenter community-based sectional survey and prospective cohort study in Sichuan, southwestern China. Eight communities were randomly selected, and the residents in each community were surveyed using a structured face-to-face questionnaire. Carotid ultrasonography and DNA information were obtained from 2,377 out of 2,893 individuals belonging to a high-risk stroke population. Genotypes of the 19 SNPs in genes involved in inflammation and endothelial function were measured. All the 2,377 subjects were followed up for 4.7 years after the face-to-face survey. The primary outcome was ischemic stroke, and the secondary outcome was a composite of vascular events. Results Among the 2,377 subjects, 2,205 (92.8%) completed a 4.7-year follow-up, 947 (42.9%) had carotid atherosclerosis [372 (16.9%) carotid vulnerable plaque, 405 (18.4%) mean IMT > 0.9 mm, 285 (12.0%) carotid stenosis ≥15%]. Outcomes occurred in 158 (7.2%) subjects [92 (4.2%) ischemic stroke, 17 (0.8%) hemorrhagic stroke, 48 (2.2%) myocardial infarction, and 26 (1.2%) death] during follow-up. There was a significant gene–gene interaction among ITGA2 rs1991013, IL1A rs1609682, and HABP2 rs7923349 in the 19 SNPs. The multivariate logistic regression model revealed that carotid atherosclerosis and the high-risk interactive genotypes among the three SNPs were independent with a higher risk for ischemic stroke (OR = 2.67, 95% CI: 1.52–6.78, p = 0.004; and OR = 3.11, 95% CI: 2.12–9.27, p < 0.001, respectively) and composite vascular events (OR = 3.04, 95% CI: 1.46–6.35, p < 0.001; and OR = 3.23, 95% CI: 1.97–8.52, p < 0.001, respectively). Conclusion The prevalence of carotid atherosclerosis was shown to be very high in the high-risk stroke population. Specific SNPs, interactions among them, and carotid atherosclerosis were independently associated with a higher risk of ischemic stroke and other vascular events.